2007
DOI: 10.1002/app.27026
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization of polybutadiene rubber with dipentamethylene thiuram tetrasulfide

Abstract: The cure of polybutadiene rubber (BR) with sulfur donor dipentamethylene thiuram tetrasulfide (DPTT) does not show reversion reaction, in contrast with similar natural rubber compounds. No polysulfure links are formed; whereas a great amount of À ÀCÀ ÀCÀ À crosslinks are produced. The addition of tetramethyl thiuram monosulfidic (TMTM) strongly affects the crosslinking process. Mechanical properties of the cured compounds are poor. In DPTT, curing of BR the radical species produced through homolitic cleavage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The formation of polysulphidic structures suggests24 that the reaction between the radical species obtained with the thermal cleavage of DPTT given in the literature34 to obtain species with higher sulfur rank,1 and also by the route of disproportionation seems to be present.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of polysulphidic structures suggests24 that the reaction between the radical species obtained with the thermal cleavage of DPTT given in the literature34 to obtain species with higher sulfur rank,1 and also by the route of disproportionation seems to be present.…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, the controversy on the nature of the action of the active sulphurating agent remains without clarity 1. In absence or presence of zinc oxide, a free‐radical mechanism,22–26 in which the active sulphurating agent is an accelerator polysulphide as shown in the Scheme , seems to fit the experimental results best.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the effect of the structures of disulfide molecules on disulfide metathesis, equimolar mixtures of DPDS/diallyl disulfide (DADS) and dibutyl disulfide (DBDS)/ dimethyl trisulfide (DMTS) pairs as well as DMTS alone were tested with CuCl 2 as the catalyst, respectively. An allyl disulfide bridge is a common constituent of sulfur crosslinkages in vulcanized rubber, 1,[16][17][18][19][20][21] while DMTS simulates polysulfidic bonds. The experiments are expected to get close to the actual situation in vulcanized rubber by choosing these reagents.…”
Section: Resultsmentioning
confidence: 99%
“…(Note: according to the accelerator/sulfur ratio, commercial sulphur vulcanization systems are usually classified into: conventional (0.1-0.6), semi-efficient (0.7-2.5), and efficient vulcanization (2.5-12). 16,17 The produced monosulfide, disulfide and polysulfide crosslinks in the total number of crosslinks amount to 0-5, 30-40 and 60-70% for conventional vulcanization, 0-20, 50-70 and 10-30% for semi-efficient vulcanization, and 40-50, 35-50 and 5-20% for efficient vulcanization, respectively [16][17][18][19][20][21][22] ). Disulfide bonds themselves have enabled self-healing of polymers through exchange or metathesis reactions by using their dynamic reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile strength enhances from 1.2 to 1.4 MPa with a decrease in elongation at the break from 150% to 105%. An appreciable increase in hardness from 44 to 53.5 Shore A was observed [18] . It has been observed that in DPPT curing, persulfenil radicals are able to produce crosslinking via allylic abstraction without disproportionation.…”
Section: Fatigue Strengthmentioning
confidence: 93%